Construction phosphorus/nitrogen-containing flame-retardant and hydrophobic coating toward cotton fabric via layer-by-layer assembly - Shi, Xiao-Hui; Liu, Qing-Yun; Li, Xue-Lin; Du, An-Ke; Niu, Jia-Wei; Li, Ying-Ming; Li, Zhi; Wang, Min; Wang, De-Yi (Polymer degradation and stability, 2022)
•Fire protection coating was successfully built on cotton fabric via LbL assembly.•The resulted cotton fabric showed self-extinguishing behavior with only 4 bilayers.•Such coating endowed fabric with promising hydrophobic property. Excellent flame-retardant cotton fabric with desired hydrophobic is of particular interests for both academia and industry. Herein, an effective multilayer coating consisting of phosphorylated polyethyleneimine (P-PEI) and hydrophobic modified ammonium polyphosphate (MAPP) was successfully constructed on cotton fabric through a facile layer-by-layer (LbL) assembly, which imparted high fire retardancy and desirable hydrophobic to the cotton fabric. Coated cotton fabric was characterized by Fourier infrared spectrometer, scanning electronic microscopy coupled with its energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy, conforming that a phosphorus- and nitrogen-containing multilayer coating was homogeneous and uniform increase on the surface of cotton fabric. The resultant cotton fabric achieved self-extinguishing in vertical burning tests and a desired hydrophobic with a water contact angle of 127.4° with only 4BL coating. Moreover, the coated cotton fabrics exhibited a slight delay of ignition accompanied by remarkably decrease of heat release and the fire growth rate index, suggesting the outstanding fire safety. The flame retardancy of coated cotton fabric was enhanced and even not ignited at the heat flux of 25 kW/m2, but the hydrophobic was almost not changed with the increase of bilayer number. Additionally, the relevant analysis of residues and volatile gases manifested that the multilayer coating contributed flame-retardant activities in both condensed- and gas-phase via forming thermally stable char residues and inhibiting the release of flammable gases. Taking advantage of the features, this high efficiency coating together with the facile finishing technique would have great potentials in application of multifunctional cotton fabrics.